Repeated high-intensity exercise modulates Ca2+ sensitivity of human skeletal muscle fibers - Gejl, K. D.; Hvid, L. G.; Willis, S. J.; Andersson, E.; Holmberg, H. C.; Jensen, R.; Frandsen, U.; Hansen, J.; Plomgaard, P.; Ørtenblad, N. (Scandinavian Journal of Medicine & Science in Sports, 2016)
The effects of short-term high-intensity exercise on single fiber contractile function in humans are unknown. Therefore, the purposes of this study were: (a) to access the acute effects of repeated high-intensity exercise on human single muscle fiber contractile function; and (b) to examine whether contractile function was affected by alterations in the redox balance. Eleven elite cross-country skiers performed four maximal bouts of 1300 m treadmill skiing with 45 min recovery. Contractile function of chemically skinned single fibers from triceps brachii was examined before the first and following the fourth sprint with respect to Ca2+ sensitivity and maximal Ca2+-activated force. To investigate the oxidative effects of exercise on single fiber contractile function, a subset of fibers was incubated with dithiothreitol (DTT) before analysis. Ca2+ sensitivity was enhanced by exercise in both MHC I (17%, P < 0.05) and MHC II (15%, P < 0.05) fibers. This potentiation was not present after incubation of fibers with DTT. Specific force of both MHC I and MHC II fibers was unaffected by exercise. In conclusion, repeated high-intensity exercise increased Ca2+ sensitivity in both MHC I and MHC II fibers. This effect was not observed in a reducing environment indicative of an exercise-induced oxidation of the human contractile apparatus